TATA KELOLA KOLABORATIVE DALAM KEBIJAKAN PUBLIK DARI PERSPEKTIVE PENANGANAN COVID -19 DKI JAKARTA - Rivelino, Rivelino; Ginting, Arwanto Harimas (Fakultas Politik Pemerintahan, 2020)
This research focuses on the urgency of collaboration between the central government and the regions in handling it. The aim is to find out how the collaboration of the DKI Jakarta government in dealing with Covid-19. This research is intended to find out the collaboration carried out by the stakeholders in handling covid-19 in Indonesia conducted by the central government and the regional government of DKI Jakarta. In this study, the sampling technique chosen by the author is using purposive sampling technique. Data validation is done by using the Triangulation method. To guarantee the validity of the data collected in this study, the author uses a source triangulation technique, which synchronizes similar data from several data sources whose information is extracted. Overall, in the three stages of the collaborative governance process in handling covid-19 disease in Jakarta there are five criteria for the success of a network or collaboration in governance that has been fulfilled namely Networked Structure, Commitment to a Common Purpose, Distributive Accountability / Responsibility, Information Sharing, and Access to Authority. This shows that the collaborative governance process in DKI Jakarta in handling covid-19 has not yet been running optimally and effectively.